Construction of prior probability distribution using a mollified functional - Yaga*†, S.J.; Dibal*, N.P.; Gongsin*, I.E.; Bakari*, H.R.; Nwaosu‡, S.C.; Wudiri§, Zara (International Journal of Mathematical Analysis and Modelling, 2023)
In this paper, we proposed a new class of prior distribution, the Mollified Functional Data Informative Prior using the convolution of standard scaled mollified functional and sampling distribution of the data. We also show that the MFDIP possesses the invariance property to reparameterization and apply the MFDIP to derive the prior for exponential probability distribution.